Meta-Representational Skills in Bullying Roles: The Influence of Definitional Competence and Empathy - Belacchi, Carmen; Benelli, Beatrice (Frontiers in Psychology, 2020)
This study investigated the influence of meta-representational aspects on bullying. Metarepresentation was operationalized in terms of the metalinguistic skill to produce conventional definitions, reflecting culturally shared representations and of the meta-level capacity to represent others' mental states underlying empathic disposition, respectively.One hundred and seventeen children, aged between 8;5 years and 10;11 years completed a definitional task and self-report questionnaires on bullying roles and empathic disposition.Descriptive, correlational and regression analyses were performed.Results confirmed that hostile roles are negatively related to definitional competence and to empathic disposition. A lack of definitional competence was the main predictor (accounting for about 16% of variance), followed by empathy (explaining a further 6% of variance) of Primary School children's disposition to assume aggressive behaviors.These findings suggest that a lack of general meta-representational abilities may hinder the development of abstract and other-centered perspective taking, and compromise (compromising) social adjustment. This implies the need to work, particularly in school, on enhancing metarepresentational and meta-linguistic skills, such as the ability to recognize mental states and verbally make explicit cultural-semantic word meaningrepresentations.